2020
DOI: 10.3748/wjg.v26.i31.4669
|View full text |Cite
|
Sign up to set email alerts
|

Initial experience of single-incision plus one port left-side approach totally laparoscopic distal gastrectomy with uncut Roux-en-Y reconstruction

Abstract: BACKGROUND Single incision plus one port left-side approach (SILS+1/L) totally laparoscopic distal gastrectomy (TLDG) is an emerging technique for the treatment of gastric cancer. Reduced port laparoscopic gastrectomy has a number of potential advantages for patients compared with conventional laparoscopic gastrectomy: relieving postoperative pain, shortening hospital stay and offering a better cosmetic outcome. Nevertheless, there are no previous reports on the use of SILS+1/L TLDG with uncut Rou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…According to a previous study, closing the afferent loop jejunum may not result in permanent healing between the mucosa and the mucosa, which is the main reason for the recanalization of the bowel. [29][30][31] This finding indicates that the linear stapler is not complete enough to close the afferent limb jejunum and needs to be further improved. Some scholars have proposed different methods of closing the afferent loop, and it has been reported that ligation with a 7-gauge silk thread can effectively reduce the recanalization rate.…”
Section: Discussionmentioning
confidence: 99%
“…According to a previous study, closing the afferent loop jejunum may not result in permanent healing between the mucosa and the mucosa, which is the main reason for the recanalization of the bowel. [29][30][31] This finding indicates that the linear stapler is not complete enough to close the afferent limb jejunum and needs to be further improved. Some scholars have proposed different methods of closing the afferent loop, and it has been reported that ligation with a 7-gauge silk thread can effectively reduce the recanalization rate.…”
Section: Discussionmentioning
confidence: 99%
“…Reduced-port laparoscopic surgery (RPS) and single-incision laparoscopic surgery (SILS) have become increasingly popular ( 12 ). As an alternative method to increase the feasibility and reduce the technical challenges of pure SILS, the single-incision plus one-port laparoscopic surgery (SILS + 1) technique has been gradually applied by an increasing number of surgical teams in recent years ( 13 , 14 ). Regarding the application of SITG + 1, most studies have only observed the short-term efficacy of SITG + 1 in distal early gastric cancer ( 5 , 15 , 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…The continuous developments in laparoscopic technology and increasing experience has meant that an increasing number of surgeons are adopting the minimally invasive approach. Many studies have introduced various methods of less invasive laparoscopic gastrectomy, such as reduced-port, dual-port, and single-port laparoscopic gastrectomy, which have contributed to the feasibility of the procedure [ 19 22 ]. However, concerns about adopting these procedures in obese patients remain due to technical difficulties and possible postoperative complications.…”
Section: Discussionmentioning
confidence: 99%